Diversity of Rickettsiales bacteria in five species of ticks collected from Jinzhai County, Anhui Province, China in 2021–2022 - Jin, Xiaojing; Liao, Jiasheng; Chen, Qingqing; Ding, Junfei; Chang, Hongwei; Lyu, Yong; Yu, Liang; Wen, Bohai; Sun, Yong; Qin, Tian (Frontiers in Microbiology, 2023)
The Rickettsiales are a group of vector-borne alphaproteo bacteria and have been recognized as important pathogens of both medical and veterinary importance. Ticks, as a group, are second only to mosquitoes as vectors of pathogens to humans and are the primary vector for pathogens of livestock, companion animals, and wildlife. Ticks are also the vector of Rickettsiales to humans and animals, playing a critical role transmission of rickettsiosis. Herein, a total of 880 ticks, including five species from three genera, were collected for examination in the present study from Jinzhai County, Lu'an City, Anhui province, China in 2021-2022. All ticks were tested by nested polymerase chain reaction (nPCR) targeting the 16S rRNA gene (rrs) and the gene fragments amplified were sequenced to detect and identify the Rickettsiales bacteria in the ticks. For further identification, the rrs-positive tick samples were further amplified by PCR targeting gltA and groEL gene and sequenced. As a result, 13 Rickettsiales species belonging to the genera Rickettsia, Anaplasma and Ehrlichia were detected, which included one tentative species of Rickettsia and three tentative species of Ehrlichia. Emerging rickettsia may be pathogenic and cause under-recognized diseases. Hence, further studies are warranted to assess the potential public health risks of the ricketsiales pathogens identified in the present study.